2018
DOI: 10.1073/pnas.1716113115
|View full text |Cite
|
Sign up to set email alerts
|

UBD modifies APOL1 -induced kidney disease risk

Abstract: People of recent African ancestry develop kidney disease at much higher rates than most other groups. Two specific coding variants in the Apolipoprotein-L1 gene termed G1 and G2 are the causal drivers of much of this difference in risk, following a recessive pattern of inheritance. However, most individuals with a high-risk genotype do not develop overt kidney disease, prompting interest in identifying those factors that interact with We performed an admixture mapping study to identify genetic modifiers of-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 35 publications
3
43
0
4
Order By: Relevance
“…Additional genetic and environmental contributors could provide a mechanism to explain both the incomplete penetrance of CKD in high-risk genotype subjects and also the clinical and pathological differences in the APOL1-associated CKDs. Preliminary studies have identified polymorphisms in NPHS2, BMP4, SDCCAG4, and UBD that modify APOL1-mediated CDK risk (7,25,64). However, a recent meta-analysis of genome-wide association data concluded there are likely few genetic factors that contribute a strong modifying second hit to APOL1-associated CKD risk and concludes the critical second-hit stressors for disease induction are more likely to be environmental (29).…”
Section: Gene-environment Interaction and Second-hit Stressorsmentioning
confidence: 99%
“…Additional genetic and environmental contributors could provide a mechanism to explain both the incomplete penetrance of CKD in high-risk genotype subjects and also the clinical and pathological differences in the APOL1-associated CKDs. Preliminary studies have identified polymorphisms in NPHS2, BMP4, SDCCAG4, and UBD that modify APOL1-mediated CDK risk (7,25,64). However, a recent meta-analysis of genome-wide association data concluded there are likely few genetic factors that contribute a strong modifying second hit to APOL1-associated CKD risk and concludes the critical second-hit stressors for disease induction are more likely to be environmental (29).…”
Section: Gene-environment Interaction and Second-hit Stressorsmentioning
confidence: 99%
“…[17][18][19] In an NS GLOM eQTL study of apolipoprotein L1 (APOL1), ubiquitin D (UBD) was significantly upregulated in individuals with a high-risk (HR) APOL1 genotype. 20 These findings were subsequently followed up in an admixture mapping study that identified enriched African ancestry at the UBD locus in people with a HR genotype and FSGS versus no FSGS and protective effects of UBD expression on the viability of cells overexpressing APOL1 risk variants, 21 providing additional support for UBD's involvement in APOL1-attributed NS.…”
Section: Introductionmentioning
confidence: 98%
“…We first plotted genes previously identified by other studies to be potential modifiers of APOL1-mediated kidney disease. A large linkage disequilibrium block on chromosome 6 containing UBD and PPP1R18 may house disease-modulating genes 26,27 , with visible differences between APOL1 genotypes in UBD and PPP1R18 expression in the tubule and endothelial clusters ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%